DIGITAL RECONSTRUCTION OF HISTORICAL SITES IN BANYUWANGI BASED ON AI AS A TEACHING MEDIUM FOR HIGH SCHOOL HISTORY SUBJECTS IN BANYUWANGI REGENCY: REKONSTRUKSI DIGITAL SITUS SEJARAH DI BANYUWANGI BERBASIS AI SEBAGAI MEDIA AJAR MATA PELAJARAN SEJARAH SMA DI KABUPATEN BANYUWANGI - Mahfud; Triana Kartika Santi; Riztika Widyasari; Wisnu (SOSIOEDUKASI, 2025)
Banyuwangi Regency possesses significant local historical potential through the presence of sites such as Songgon Cave, Wongsorejo Cave, Kalipuro Cave, and the Neolithic Site of Kendenglembu. These resources have not yet been optimally utilised within the history learning process at the upper secondary school level. This study aims to develop a digital instructional medium based on artificial intelligence that reconstructs local historical sites in a visual and educational manner. The research employs a 4D model of Research and Development (R&D), comprising the stages of define, design, develop, and disseminate. The sample includes 200 upper secondary school students selected through stratified purposive sampling. Data collection techniques encompass pre-tests and post-tests, expert validation, observation, and interviews with local community members. The results show that expert validation yielded a feasibility score of 92% and usability of 89%. The students’ pre-test score was 61.4, increasing to 84.7 in the post-test, with an effectiveness value of Cohen’s d at 1.72. The media is deemed highly suitable for use in local wisdom-based history learning. This research recommends further development in integrating virtual reality and enhancing visual data through GIS. AI-based media is expected to reinforce contextual, immersive, and relevant local history learning for the current digital generation.